Treatment of refractory thrombotic thrombocytopenic purpura with N‐acetylcysteine: a case report. Issue 5 (9th October 2013) - Li, Gloria W.; Rambally, Siayareh; Kamboj, Jasmine; Reilly, Sean; Moake, Joel L.; Udden, Mark M.; Mims, Martha P.
<x xml:space="preserve">Abstract</x> Background Thrombotic thrombocytopenic purpura (TTP) is a life‐threatening disease resulting in systemic microvascular thrombosis. The disease is caused by excessive platelet (PLT) adhesion to ultra‐large (UL) von Willebrand factor (VWF) multimers inadequately cleaved by the processing enzyme ADAMTS‐13. While many cases respond to plasma exchange performed with or without concurrent corticosteroids, treatment of the 10% to 20% of patients with refractory disease is difficult. Experimental studies demonstrating that N‐acetylcysteine (NAC) inhibits PLT binding to endothelial cell–secreted and anchored UL VWF multimers suggest that NAC may be useful in the treatment of TTP. Case Report A 44‐year‐old woman presented with malaise, confusion, chest and abdominal pain, and transient visual loss. Laboratory results and peripheral blood smear were consistent with TTP. The patient was begun on plasma exchange and corticosteroid treatment, but after 10 days the PLT count was still less than 10.0 × 109/L and she developed a fever. Rituximab was initiated, but the patient's condition worsened and she became comatose. Antibiotics were initiated, but cultures remained sterile. After 3 days of coma and further clinical deterioration, treatment with NAC was begun. The patient received a loading dose of 150 mg/kg NAC intravenously (IV) over 1 hour. Within 18 hours the patient awakened abruptly and began communicating with medical personnel. Plasma exchange, corticosteroids, rituximab, and NAC infusion (150 mg/kg IV over 17 hr daily × 10 days) were continued and by Day 17 the PLT count was more than 50 × 109/L. The patient fully recovered and was discharged on Day 31. Conclusion This is the first complete report of a TTP patient treated with NAC. NAC was a safe and effective supplementary treatment for refractory TTP in this patient.